Exergetic, energetic and environmental dimensions - Dinçer, İbrahim 1964-; Colpan, Can Ozgur; Kizilkan, Onder (London Academic Press, 2018)
This edited book looks at recent studies on interdisciplinary research related to exergy, energy, and the environment. This topic is of prime significance – there is a strong need for practical solutions through better design, analysis and assessment in order to achieve better efficiency, environment and sustainability. Exergetic, Energetic and Environmental Dimensions covers a number of topics ranging from thermodynamic optimization of energy systems, to the environmental impact assessment and clean energy, offering readers a comprehensive reference on analysis, modeling, development, experimental investigation, and improvement of many micro to macro systems and applications, ranging from basic to advanced categories.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Exergy -- Environmental aspects; Power resources -- Environmental aspects; Electronic books